A University Senate for All - Engstrand, Gary (Academe, 2005)
The University of Minnesota's University Senate was established in 1912. At the time the proposal to expand it was developed in 2003, the senate had two subordinate bodies, the Faculty Senate and the Student Senate. Although the subordinate bodies could and did take action on their own, most of their actions were subject to final approval by the University Senate. Matters related to faculty tenure and judicial proceedings related to claims about tenure were exceptions in that they were confined to the Faculty Senate--but even this exception was carved out in the University Senate constitution, so it could be changed. The plan that was developed proposed that the membership categories of the University Senate be rearranged so that all of the major groups at the university would be represented. This change in membership would permit all groups to participate in discussions of issues that affected them or the university as a whole. The University Senate constitution provides that constitutional amendments require an absolute two-thirds vote at one meeting or an absolute majority at two consecutive meetings. The president rarely disapproves senate constitutional amendments. In this case, the transmission was uncontroversial, because both the university president and the senior vice president for academic affairs and provost expressed strong support for the reorganization. The university's board of regents approved the constitutional revisions in February 2005. Elections will be held in spring 2005, and the new structure will be in place July 1, 2005. (Contains 1 note.)